Reclamation of Forward Osmosis Reject Water Containing Hexavalent Chromium Via Coupled Electrochemical-Physical Processes - Sandoval, A; Sandoval, A (Taylor and Francis Ltd., 2024)
Forward osmosis is a water separation process that uses the natural energy of osmotic pressure to separate water from dissolved solutes through a semipermeable membrane. One of the major challenges using this process is the rejection water which contains high content of pollutants, hindering its practical application. Herein, for the first time, this work introduces a coupled electrochemical-physical process including iron-electrocoagulation/filtration/sedimentation as a cost-effective treatment to the forward osmosis reject water containing hexavalent chromium to be reclaimed. The synergistic treatment was optimized through a central composite design and response surface methodology to enhance hexavalent Cr removal and minimize operating costs, electrical energy consumption, and settled sludge volume. A 90.0% chromium removal was achieved under optimized conditions: electrolysis time of 59.7 min and current of 1.24 A (J = 6.32 mA cm−2). In addition, operating costs of 0.014 USD m−3, electrical energy consumption of 0.005 kWh m−3, and settled sludge volume of 445 mL L−1 were obtained. © 2022 Informa UK Limited, trading as Taylor & Francis Group.